The thundering prairie - Hancock, M. A. (Mary A.); Hall, H. Tom; Larry Dingman Western Fiction Collection (Library of Congress) (Philadelphia : Macrae Smith Company, 1969)
When the Cherokee Strip is opened in 1893, bad luck leaves thirteen-year-old Benjy Bryan with the responsibility of winning the race for the homestead Claim on which his family has gambled everything.
Keywords: Oklahoma -- History -- Fiction; Dust jackets (Binding) -- Pennsylvania -- Philadelphia -- 20th century